Exogenous interleukin‐2 can rescue in‐vitro T cell activation and proliferation in patients with a novel capping protein regulator and myosin 1 linker 2 mutation. (18th April 2020) - Shamriz, O.; Simon, A. J.; Lev, A.; Megged, O.; Ledder, O.; Picard, E.; Joseph, L.; Molho-Pessach, V.; Tal, Y.; Millman, P.; Slae, M.; Somech, R.; et al.
Summary: Capping protein regulator and myosin 1 linker 2 (CARMIL2) deficiency is characterized by impaired T cell activation, which is attributed to defective CD28‐mediated co‐signaling. Herein, we aimed to analyze the effect of exogenous interleukin (IL)‐2 on in‐vitro T cell activation and proliferation in a family with CARMIL2 deficiency. This study included four children (one male and three females; aged 2·5–10 years at presentation). The patients presented with inflammatory bowel disease and recurrent viral infections. Genetic analysis revealed a novel homozygous 25‐base pairs deletion in CARMIL2 . Immunoblotting demonstrated the absence of CARMIL2 protein in all four patients and confirmed the diagnosis of CARMIL2 deficiency. T cells were activated in‐vitro with the addition of IL‐2 in different concentrations. CD25 and interferon (IFN)‐γ levels were measured after 48 h and 5 days of activation. CD25 surface expression on activated CD8 + and CD4 + T cells was significantly diminished in all patients compared to healthy controls. Additionally, CD8 + T cells from all patients demonstrated significantly reduced IFN‐γ production. When cells derived from CARMIL2‐deficient patients were treated with IL‐2, CD25 and IFN‐γ production increased in a dose‐dependent manner. T cell proliferation, as measured by Cell Trace Violet, was impaired in one patient and it was also rescued with IL‐2. In conclusion, we found that IL‐2 rescued T cell activation and proliferation in CARMIL2‐deficient patients. Thus, IL‐2 should be further studied as a potential therapeutic modality for these patients. Abstract : CARMIL2 deficiency is characterized by impaired T cell activation and proliferation, recurrent infections and reduced regulatory T cell counts. Interleukin (IL‐2) can rescue in‐vitro T cell activation and proliferation of CARMIL2‐deficient patients. IL‐2 should be further studied as a potential therapeutic modality in CARMIL2‐deficient patients.